Barriers and Difficulties of Students in the Mathematics Learning Process in Junior High Schools - Asdar Ahmad; Loso Judijanto; Jeranah; Jitu Halomoan Lumbantoruan; Muhammad Ichsan Abda (LPPM Undiksha, 2024)
Low math learning outcomes in students, especially in comparison materials, are reflected in low scores on the National Exam and learning outcomes in the classroom. Several factors, both internal and external, can cause learning difficulties experienced by students. This study aims to analyze the obstacles to students' difficulties in learning mathematics and their causes. The subjects involved were 30 students. This type of mixed research uses data collection methods through tests, interviews, and questionnaires. The instruments used are closed questionnaire sheets and interview guidelines. Data analysis techniques using data collection are interactive model data analysis techniques, especially in the data reduction and conclusion drawing sections. The results revealed that 12 students experienced difficulties in interpreting language. These difficulties include difficulty understanding the problem's core and integrating everyday language into the depth of mathematical language. The conclusion that can be formulated is that the difficulties experienced by students arise because of themselves and from people around their school environment. This research implies that educators design materials by improving concepts and mathematical literacy to overcome student difficulties.